Bond Strength Assessment for Different Types of Repair Materials - Aseel S. Mansi (Engineering and Technology Journal, 2010)
The main objective of this work is to evaluate the bond strength fordifferent types of repair materials. Three test methods; slant shear, splitting prism and Bi-Surface shear test with conventional and two polymer modified repair mortars were used, The conventional mortar (MC), polymer modified mortar (MSBR) was prepared by admixing SBR 15% of cement weight, polymer modified and fiber reinforced repair mortar named commercially Cempatch S (MCS) was prepared by mix Cempatch S with a water ratio of 0.2. The results show that the use of SBR and Cempatch S improves the bond strength of repair mortar compared with conventional repair mortar but the percentage increased with Cempatch S was greater than SBR. The percentage increase in bond strength for concrete substrate repaired with Mcs (CMcs) were 52.67, 174.8, and 46.7% for Slant Shear, Splitting Prism and Bi-Surface shear testrespectively relative to the corresponding repaired with conventional mortar MC(CMC); while, the corresponding percentages increase for concrete substrate repaired with MSBR (CMSBR) was 45.13, 129 and 30%. It is found that the bond strengths obtained from some tests was up to an average of four times larger than those obtained from others.